2013
DOI: 10.3136/fstr.19.409
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical Characterization of Seed Oils Extracted from Oranges (Citrus sinensis)

Abstract: This study aimed to characterize the seeds of oranges, varieties Hamlin, Natal, Pera-rio and Valencia, on the composition and physico-chemical properties of its oil through the determination of free fatty acids, peroxide value, refraction, iodine value, saponification value, unsaponifiable matter, oxidative stability and fatty acid profile. The results were submitted to analysis of variance and differences between the average results were tested at 5% probability by Tukey test. The orange seed oils showed high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Total Carbohydrate was estimation shows 8.326 ± 0.003844 µg/ml on peel extract of ripening large sample with signi cance (P< 0.0001) (Table I), However Athira et al (2017) revealed Citrus maxima with carbohydrate content of 3.690±0.705 mg/ml followed by Citrus limonum 3.073±0.001mg/ml. The free amino acid (FAA) of the sample was has a concentration of 24.35± 0.0225 µg/ml shown by peel extract of ripening large sample and Free fatty acid value of 373.9 (µg KOH/ml) is reported in pulp extract of ripening large sample (Table I), reportedly Valencia orange found to have free fatty acid of 0.27 ± 0.03a meq/kg (Caroline et al 2013). The 2, 2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity computed to be 73.80% highest among the extracts used (Table II and Fig 4), by comparing the standard (Ascorbic acid -14% ) it is found that citrus extracts are having higher scavenging activity other studies conducted shows 85% of scavenging activity on Citrus reticulate (Vinita et al 2016).…”
Section: Resultsmentioning
confidence: 96%
“…Total Carbohydrate was estimation shows 8.326 ± 0.003844 µg/ml on peel extract of ripening large sample with signi cance (P< 0.0001) (Table I), However Athira et al (2017) revealed Citrus maxima with carbohydrate content of 3.690±0.705 mg/ml followed by Citrus limonum 3.073±0.001mg/ml. The free amino acid (FAA) of the sample was has a concentration of 24.35± 0.0225 µg/ml shown by peel extract of ripening large sample and Free fatty acid value of 373.9 (µg KOH/ml) is reported in pulp extract of ripening large sample (Table I), reportedly Valencia orange found to have free fatty acid of 0.27 ± 0.03a meq/kg (Caroline et al 2013). The 2, 2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity computed to be 73.80% highest among the extracts used (Table II and Fig 4), by comparing the standard (Ascorbic acid -14% ) it is found that citrus extracts are having higher scavenging activity other studies conducted shows 85% of scavenging activity on Citrus reticulate (Vinita et al 2016).…”
Section: Resultsmentioning
confidence: 96%
“…Copper 29 and C. sinensis (Hamlin) from Brazil. 5 However, the proximate content of C. sinensis seed oil notwithstanding the species variation continues to be excellent nutritional and beneficial seed oil, and also a source of quality edible oils. 8 The fatty acid components present in sweet orange Citrus sinensis seed oil were identified by Gas Chromatography-Mass Spectrometry (GC-MS) analysis.…”
Section: Discussionmentioning
confidence: 99%
“…3 It has a total global production of about 120 million tons, so it is considered one of the most important and widely grown fruit crops. 4,5 The area planted to citrus in the world is approximately 7.62 million hectares. 5,6,4 Correspondingly, the citrus industry, has demonstrated a great growth potential, being one of the most competitive agricultural sectors among the countries with a tropical and subtropical climate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations